Variations in Soil Bacterial Community Diversity and Structures Among Different Revegetation Types in the Baishilazi Nature Reserve - Deng, Jiaojiao; Yin, You; Zhu, Wenxu; Zhou, Yongbin (Frontiers in Microbiology, 2018)
We compared patterns of soil bacterial community diversity and structure in six secondary forests (JM， Juglans mandshurica; QM, Quercus mongolica; MB, mixed Broadleaf forest; BE, Betula ermanii; CB, conifer-broadleaf forest; PT, Pinus tabuliformis) and two plantation forests (LG, Larix gmelinii; PK, Pinus koraiensis) of the Baishilazi Nature Reserve, China, based on the 16S rRNA high-throughput Illumina sequencing data. The correlations between the bacterial community and soil environmental factors were also examined. The results showed that the broadleaf forests (JM, QM, MB) had higher levels of total C (TC), total N (TN), available N (AN), and available K (AK) compared to the coniferous forests (PT, LG, PK) and conifer-broadleaf forest (CB). Different revegetation pathways had different effects on the soil bacterial community diversity and structure. For the α-diversity, the highest Shannon index and Simpson index were found in JM. The Simpson index was significantly positively correlated with the available P (AP) (P<0.05), and the Shannon index was significantly positively correlated with AK (P<0.05). Compared with others, the increased ACE index and Chao1 index were observed in the CB and MB, and both of these α-diversity were significantly negative with AK (P<0.05). The relative abundances of bacterial phyla and genera differed among different revegetation types. At the phylum level, the dominant phylum groups in all soils were Proteobacteria, Acidobacteria, Actinobacteria, Verrucomicrobia, Chloroflexi, Bacteroidetes, Gemmatimonadetes, and Planctomycetes. Significant differences in relative abundance of bacteria phyla were found for Acidobacteria, Actinobacteria, Chloroflexi, Gemmatimonadetes, and Proteobacteria. Correlation analysis showed that Soil pH, TC, TN, AP, and AK were the main abiotic factors structuring the bacterial communities. As revealed by the clear differentiation of bacterial communities and the clustering in the heatmap and in the PCA plots, broadleaf forests and coniferous forests harbored distinct bacterial communities, indicating a significant impact of the respective reforestation pathway on soil bacterial communities in the Baishilazi Nature Reserve.